The social organization of knowledge in eleven South African primary schools - Wilburn, Shelly Anna (School of Education, 2017)
This dissertation is motivated by systemic disparities in student academic achievement and teacher knowledge along lines of socio-economic status. From an investigation of eleven differentially performing primary schools located in contexts of poverty, the study shows how knowledge is 'unlocked' or maximized through forms of instructional communication between teachers and with school managers. Knowledge is foregrounded as a critical resource to teachers and as the means by which the purpose of the school is achieved. To investigate how knowledge circulates, the study recruits conceptual resources from Bernstein (1971; 1975; 2000), Douglas (1996), Durkheim (1933), and Weber (1947) and draws empirical tools from the fields of school organization, leadership and management, and teacher professional community. Two key dimensions frame the study of the school in which meanings, and potentially knowledge, are circulated and shaped. These are the specialization of communication, which organizes, classifies, and differentiates 'what' forms of knowledge circulate, and the form of teachers' relations, which structures communication and controls 'how' knowledge circulates. These two axes of variation - the 'what' and 'how' of communication - are used to describe and classify the instructional order of each school. From qualitative analyses of interview data obtained from grade 3 teachers, Heads of Department, and principals at each school over three years, significant differences emerge along lines of academic performance. Between teachers, a professional mode of instructional order is found to facilitate the circulation of knowledge in schools performing better than expected, where relations are open, differences in expertise are recognized, and teachers share and/or develop pedagogic strategies. Between teachers and school managers, the circulation of knowledge is made possible through either the professional or the bureaucratic mode based upon formal status and expertise, also associated with relatively better academic outcomes. Where communication is weakly specialized through routinized processes based upon status only, findings suggest the circulation of knowledge is impeded by the displacement of expertise, which manifests in schools performing lower than expected. Findings imply that the tipping point in the achievement of higher academic outcomes lies in the establishment of an instructional order that maintains organizational stability based upon status and that develops pedagogic strategies through expertise. The study shows how communication, as a central organizational process, serves as a medium for control and a potential agent of educational change.